Age and gender differences in expressive flexibility and the association with depressive symptoms in adolescents - Zhang, Shaohua; Liu, Junsheng; Sang, Biao; Zhao, Yuyang (Frontiers in Psychology, 2023)
Objective This study investigated age and gender differences in the ability to flexibly enhance and suppress facial expressions according to situational demands, known as expressive flexibility (EF), as well as its relationship with depressive symptoms in adolescents. Methods The participants included 766 Chinese high school students aged between 12 and 18 years (mean age = 14.96 years, standard deviation = 2.04; 52.2% female). Data on EF and depressive symptoms were collected using self-report questionnaires. Results Girls scored higher on enhancement abilities than boys, but with no significant gender difference in suppression abilities. There were also no significant age-related differences in enhancement and suppression abilities. Only enhancement ability was negatively associated with depressive symptoms. Conclusion The development of EF abilities was stable among adolescents, with varying effects in terms of gender, and the importance of EF and enhancement abilities in reducing depressive symptoms in adolescents was highlighted.